REVITALISASI POTENSI SAUJANA BUDAYA KAWASAN PERDESAAN KREBET YOGYAKARTA BERBASIS PADA AKTIVITAS EKO-EKONOMI - Soeroso, Amiluhur; Susilo, Y. Sri (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2008)
This research aims to profile precisely strategy for the cultural landscape revitalization of Krebet region with an eco-economy approach. Data were obtained from 200 person of community which doing acitivity in Krebet with structured questionnaire; and conducted by using both factor and cluster analysis. After that, as a result of Delphi method, the policy was shaped by exploring 15 experts. The priorities of policy are confirmed by analytic hierarchy process (AHP). The results indicate that revitalization indicators of Krebet’s cultural landscape are: (1) eco-museum (conservation of panoramic landscape and traditionally agriculture) and conservation of forestry function (biodiversity management and planting various trees); (2) eco-culture (uses local resources, living culture conservation and handicraft innovation) and cultural heritage conservation (traditional arts and cultural heritage). All utilizing of the attributes based on eco-economy that respects an environmentally sustainable economy. It requires that the principles of ecology establish the framework for the formulation of economic policy and that economists and egologist work together to fashion the new economy. Hence, an eco-economy is perhaps a new paradigm to an immediate needed change. For the reason, the survival of Krebet’s site in the future will fully depend on its sustainable development policy to those attributes. Management of cultural landscape in Krebet should have to focus on natural and cultural – a cultural landscape – resources where human being living.Keywords: Krebet, cultural landscape, eco-economy, revitalization